Professor, dean and rector of Saratov university Vladimir V. Golubev. 2. “The twelve-year stay in Saratov played an exceptional meaning in my life” - Anikin, Valery Mikhailovich (Известия Саратовского университета. Новая серия Серия: Физика, 2022)
Background and Objectives: The second part of the article about Vladimir V. Golubev consists of materials reflecting a significant period of his life from 1917 to 1930, which he spent in Saratov as a professor at Saratov University and other higher educational institutions of the city. Materials and Methods: The main milestones of the Saratov period of Vladimir V. Golubev are presented in accordance with the autobiographical and documentary materials stored in the archive of Saratov University, as well as his memoirs, the memoirs of his Saratov colleagues and students. His multifaceted (educational, scientific, organizational, educational) activities, the professorial environment are illuminated against the background of the socio-political situation characteristic of the 1920s (economic devastation, hunger, peasant unrest, difficult living conditions, ambiguous management decisions in the field of higher education). The “proletarianization” of higher education implemented by the authorities in the first post-revolutionary years was essentially reduced to the slogan: “You give higher education, bypassing secondary education!” In practice, this was expressed in the filling of universities with students who did not have the necessary previous education, in the class approach when choosing “nominees” for graduate school, giving the “proletarian students” managerial functions. Vladimir V. Golubev, as a rector, was also given the job of creating a pedagogical faculty of Saratov State University to replace the physics and mathematics department and some other divisions of the university. In 1922, during the rectorship of Vladimir V. Golubev, permission was obtained to assign the name of Nikolai G. Chernyshevsky to Saratov University. Conclusion: An analysis of the sources shows that during the years of work at Saratov University, the brilliant lecturing qualities of Vladimir V. Golubev and his great scientific gift were clearly manifested and formed.